Ownership structure and corporate social responsibility in an emerging market - Sahasranamam, Sreevas; Arya, Bindu; Sud, Mukesh (Asia Pacific journal of management, 2020)
While scholarship exploring the impact of ownership structure on corporate social responsibility (CSR) has investigated firms in developed markets, less work has examined how ownership in firms from emerging markets influences community-related CSR. Both internal and external forces potentially drive community-related CSR decisions. It is hence important to understand the role of internal constraints arising due to agency problems along with institutional pressures from external stakeholders in emerging markets in shaping CSR. In this study, we draw on agency theory and sociological perspectives of institutions to explore variations in the motivation of different owners to pursue a socially responsible agenda. Our analysis of a sample of Indian firms for the period 2008–2015 illustrates that business group and family ownership is beneficial for community-related CSR. Our theoretical arguments and results highlight the importance of combining multiple lenses to assess the influence of ownership structures on CSR in emerging markets.